2015
DOI: 10.3311/ppci.7128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Application of Thin HMA Overlay on the Existing Flexible Pavement for High-Traffic-Volume Rural Highways

Abstract: Thin hot mix asphalt (HMA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A system of triggers that comprise various distress threshold values, including IRI and rutting, were then used to determine proper rehabilitation methods based on the rating results. Koohmishi and Palassi employed the MEPDG software to determine the appropriate time for application of thin asphalt overlay layer for typical flexible pavements that can service for 10 years without a necessity of structural overlay and then applied overlay layers on the existing pavement surface to investigate the overlay serviceability life ( 23 ). The results showed that the thin asphalt overlay layer extended the pavement service life significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A system of triggers that comprise various distress threshold values, including IRI and rutting, were then used to determine proper rehabilitation methods based on the rating results. Koohmishi and Palassi employed the MEPDG software to determine the appropriate time for application of thin asphalt overlay layer for typical flexible pavements that can service for 10 years without a necessity of structural overlay and then applied overlay layers on the existing pavement surface to investigate the overlay serviceability life ( 23 ). The results showed that the thin asphalt overlay layer extended the pavement service life significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pavement repairing and maintenance are important works in road engineering. As the service time of the roads increases, problems such as insufficient friction, surface cracking, performance degradation, and appearance defects might occur to road surface, so targeted solutions are required for solving these issues [1]. Thin-layer overlays have received extensive attention ever since their inception.…”
Section: Introductionmentioning
confidence: 99%